Morphological and Molecular Diversity in Turkish Sesame Germplasm and Core Set Selection. Issue 2 (1st March 2015) - Frary, Anne; Tekin, Pelin; Celik, Ibrahim; Furat, Seymus; Uzun, Bulent; Doganlar, Sami
ABSTRACT: The conservation of plant germplasm is essential to ensure future breeding gains and crop bio‐diversity. To be truly useful, such germplasm must be characterized for morphological traits and genetic diversity. In this work, agro‐morphological diversity was assessed in 137 Turkish sesame ( Sesamum indicum L.) genotypes (129 accessions and eight cultivars) by examination of eight qualitative and nine quantitative traits. As expected, morphological variability in the cultivars was low with broader diversity present in sesame accessions. However, some accessions were identified with interesting features, such as increased number of capsules and seed yield, which could be employed in future cultivar development. The sesame genotypes were analyzed for molecular genetic diversity with 140 amplified fragment length polymorphism (AFLP) loci. The results indicated a relatively low level of variability with an average dissimilarity value of 0.33 for all genotypes. Population structure was also examined and indicated that the material fell into two subpopulations. As most of the accessions (82%) were obtained from the U.S. Department of Agriculture (USDA) and are not yet housed in the Turkish national sesame germplasm collection, the data were used to identify a core set of 22 accessions that should be preserved in Turkey. The importance of using both molecular and morphological data for core selection is highlighted with a focus on germplasm preservation and breeding.